Fexofenadine and Rosuvastatin Pharmacokinetics in Mice with Targeted Disruption of Organic Anion Transporting Polypeptide 2B1 - Medwid, Samantha; Li, Mandy M.J.; Knauer, Michael J.; Lin, Kathleen; Mansell, Sara E.; Schmerk, Crystal L.; Zhu, Catherine; Griffin, Katelyn E.; Yousif, Mohamed D.; Dresser, George K.; Schwarz, Ute I.; Kim, Richard B.; et al. (Drug metabolism and disposition, 2019)
Organic anion transporting polypeptide 2B1 (OATP2B1) is a widely expressed membrane transporter with diverse substrate specificity. In vitro and clinical studies suggest a role for intestinal OATP2B1 in the oral absorption of medications. Moreover, OATP2B1 is highly expressed in hepatocytes where it is thought to promote liver drug clearance. However, until now, a shortcoming of studies implicating OATP2B1 in drug disposition has been a lack of in vivo models. Here, we report the development of a knockout (KO) mouse model with targeted, global disruption of the Slco2b1 gene to examine the disposition of two confirmed mOATP2B1 substrates, namely, fexofenadine and rosuvastatin. The plasma pharmacokinetics of intravenously administered fexofenadine was not different between KO and wild-type (WT) mice. However, after oral fexofenadine administration, KO mice had 70% and 41% lower maximal plasma concentration (Cmax) and area under the plasma concentration-time curve (AUC0–last) than WT mice, respectively. In WT mice, coadministration of fexofenadine with grapefruit juice (GFJ) or apple juice (AJ) was associated with reduced Cmax by 80% and 88%, respectively, while the AUC0–last values were lower by 35% and 70%, respectively. In KO mice, AJ coadministration reduced oral fexofenadine Cmax and AUC0–last values by 67% and 59%, respectively, while GFJ had no effects. Intravenous and oral rosuvastatin pharmacokinetics were similar among WT and KO mice. We conclude that intestinal OATP2B1 is a determinant of oral fexofenadine absorption, as well as a target for fruit juice interactions. OATP2B1 does not significantly influence rosuvastatin disposition in mice. A novel mouse model with targeted disruption of the Slco2b1 gene revealed that OATP2B1 is a determinant of oral absorption but not systemic disposition of fexofenadine, as well as a target of fruit juice interactions. Rosuvastatin oral and intravenous pharmacokinetics were not dependent on OATP2B1. These findings support the utility of the Slco2b1 KO mouse model for defining mechanisms of drug disposition at the intersection of in vitro and clinical pharmacology.